2010
DOI: 10.1007/s11746-009-1527-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Irrigation Regimes on Oil Content and Composition of Safflower (Carthamus tinctorius L.) Cultivars

Abstract: Safflower oil contains a large amount of unsaturated fatty acids, however, the composition of the oil may be affected by drought stress. This experiment determined the effect of three irrigation regimes (60, 75 and 90% soil moisture depletions of available water) on oil composition of safflower cultivars (Kuseh, PI and IL111).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
42
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 16 publications
10
42
1
Order By: Relevance
“…These results are in agreement with those of Ashrafi and Razmjoo (2010) in safflower and Dornbos and Mullen (1992) in soybean, who also observed oil content reductions due to drought stress. Oil concentration is not only affected by drought stress but was also shown to highly depend on the genotype (Blum, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with those of Ashrafi and Razmjoo (2010) in safflower and Dornbos and Mullen (1992) in soybean, who also observed oil content reductions due to drought stress. Oil concentration is not only affected by drought stress but was also shown to highly depend on the genotype (Blum, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…We observed that drought globally reduces sesame seed oil content of the five genotypes but the remaining seed components fluctuated according to the genotypes. Similar findings were reported in other important oilseed crops such as canola [46], soybean [47] and safflower [48].…”
Section: Does Drought Resistance Maintain Good Seed Quality In Sesame?supporting
confidence: 88%
“…Safflower oil contains a large amount of unsaturated fatty acid; however, the composition of the oil was not affected by drought. However, drought reduces the palmitic, stearic, oleic, and linoleic acid contents (Ashrafi and Razmjoo 2010). Fig.…”
Section: Seed Oil Yield and Qualitymentioning
confidence: 96%